Ordinary Letters: Contextual Research Method - Šmitienė, Giedrė (Tautosakos darbai, 2018)
In broadest sense, this article deals with ordinary writing, ordinary people and everyday life that researchers find hardly accessible and antidisciplinary. The author pursues two definite interrelated goals. First, it is identifying the nature of letters by poet Janina Degutytė and working out an appropriate method for their primary investigation. The second goal stems from the nature of these letters and the circle of the poet’s correspondents: that is revealing the field of letters covered by unauthoritative, ordinary people. Epistolary heritage by the Lithuanian poet Janina Degutytė (1928–1990) comprises correspondence with her closest female friends and acquaintances, none of whom (with only one exception) worked as culture professionals. Several tactics emerge from Degutytė’s letters, including bonding (when nothing particular needs to be conveyed, yet letter aims at keeping in touch), business matters (today best arranged by phone), and – rarely – narration (when writing from a place unfamiliar to the addressee). Such mode of writing can be adequately defined by the notion of ordinary or everyday writing (Daniel Fabre). Rather than indicating some lack, such definition reveals the essential quality of the letters. Ordinary letters invite asking simple questions stemming from them as such and looking for the most relevant ways of answering. Inductive approach produces three tactics of contextualization. The first one recreates the field of letters composed of letters by the participants of the correspondence and partly – of letters written by the main characters acting in Degutytė’s letters. Seven hundreds of letters written by the poet are presented together with numerous other letters. This allows for understanding the poet’s life among the lives of other people. The second tactic is fieldwork, which is suitable because the letter research is conducted at the time when contacting many of the poet’s correspondents and people mentioned in her letters is still possible. Interviews with these people particularly well elucidate the public and hidden conditions of life in the soviet Lithuania from 1950s to 1980s that were also mentioned in the letters. The third tactic employs investigating periodicals as quotidian press. Among other things, this enables discovering some hitherto unknown poems by Degutytė or different versions of her popular poems, published in newspapers and magazines. In general, this reveals variation in her work, its changeability resulting from modifications introduced by the author and her editors. All these three tactics reach outside the textual boundaries of letters and reveal their different contexts. This answers the requirements inherent in the nature of letters, since they, especially the ordinary ones, are characterized by metonymic language that points to the writing situation and denotes the lived life. This case proves that separation between text and context should not be overestimated. Another point stemming from the contextual research – all the tactics serve to create a polyphonic and polycentric view. Individual voices correct and modify each other, not falling into one coherent line. All this makes prerequisites for their kaleidoscopic, rather than microscopic, investigation (Liz Stanley). Ordinary letters written by a person who acts as a culture professional leads us into the field of letters written by ordinary people, enabling understanding them as a research subject still absent from the Lithuanian cultural studies, yet definitely worthy of them. Besides, all these epistles uncover simplicity of the lived life, providing researcher with a rare possibility to observe the daily distribution of attention, care, time and energy, along with intentionality of consciousness that is seldom available to investigation.